2016
DOI: 10.1002/macp.201600117
|View full text |Cite
|
Sign up to set email alerts
|

High Internal Phase Emulsion Ring‐Opening Polymerization of Pentadecanolide: Strategy to Obtain Porous Scaffolds in a Single Step

Abstract: Single‐step process for production of porous scaffold based on poly(pentadecanolide) (PPDL) is reported. The scaffold is produced via in situ porosity generation during ring‐opening polymerization (ROP) of the lactone pentadecanolide (PDL) in high internal phase emulsion (HIPE) using a water soluble enzyme (Lipase TL) as catalyst. The enzyme present in dispersed aqueous phase of HIPE effectively carries out ROP of monomer present in continuous oil phase. The polymerization occurs at the interface of oil and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…ROP of cyclic monomers within HIPEs has met with limited success. Pentadecanolide, a lactone monomer, was polymerized in a w/o HIPE by using a water-soluble enzyme catalyst, Lipase TL . While the monomer was in the external phase, the ROP occurred at the interface since the catalyst was located in the internal phase, with both the rate and the degree of polymerization increasing with increasing catalyst concentration.…”
Section: Polymerization Chemistrymentioning
confidence: 99%
“…ROP of cyclic monomers within HIPEs has met with limited success. Pentadecanolide, a lactone monomer, was polymerized in a w/o HIPE by using a water-soluble enzyme catalyst, Lipase TL . While the monomer was in the external phase, the ROP occurred at the interface since the catalyst was located in the internal phase, with both the rate and the degree of polymerization increasing with increasing catalyst concentration.…”
Section: Polymerization Chemistrymentioning
confidence: 99%
“…Development of PolyHIPEs by ring-opening polymerisation (ROP) of cyclic monomers is a relatively new route of polymerisation HIPEs. ε-caprolactone and L-lactide are the most widely used monomers in this approach (Pérez-García et al, 2016;Sharma et al, 2016;García-Landeros et al, 2019;Utroša et al, 2019;Yadav et al, 2019). One of the most important advantages of this technique is the elimination of diluting solvents from the emulsion composition due to the low viscosity of the cyclic monomers.…”
Section: Ring-opening Polymerisationmentioning
confidence: 99%
“…An already reported strategy of using enzyme catalyzed ROP for the synthesis of poly(pentadecanolide) scaffolds using w/o HIPE templates also did not work for CL. 95 HIPE templating for CL, therefore, required the use of a non-aqueous emulsion where such issues could be resolved. Few studies have recently been reported where the synthesis of PCL scaffolds (neat, blend or crosslinked) was performed using nonaqueous HIPE templates comprising hydrophobic liquids such as olefins or silicone oil as the dispersed phase.…”
Section: Non-aqueous Hipe Templatesmentioning
confidence: 99%